Visual digital culture : surface play and spectacle in new media genres - Darley, Andrew. (Routledge, 2000)
A back story. Genealogy and tradition. Shaping tradition. Simulation and hyperrealism. The waning of narrative. The digital image in 'the age of the signifier'. Games and rides. Surface play and spaces of consumption.